Exploring education students' use of ChatGPT for academic and personal purposes: insights from a developing country context - Gasaymeh, AlMothana; Abu Qbeita, Asma'a; AlMohtadi, Reham; Beirat, Mohammad (Frontiers in Education, 2025)
Generative Artificial Intelligence (AI) has become popular and has changed how we do things. Generative AI has an impact on educational systems. One of the popular types of Generative AI is ChatGPT. Using ChatGPT presents both benefits and challenges for students. It is important to understand how our students are using this technology. This study examines Jordanian education students' use of ChatGPT for personal and academic purposes and the differences in usage based on gender and academic level. The study followed a descriptive research design in which 134 participants completed an online questionnaire. The results showed that students' use of ChatGPT for personal and academic purposes was generally moderate, with tasks such as generating translations and writing prompts to generate short, creative ideas or themes for writing assignments being the most frequently used features. Students' use of ChatGPT for personal purposes slightly exceeded their academic use of the tool, but no significant differences were observed based on gender or academic level. Despite the proven benefits of ChatGPT, the findings highlight that ChatGPT is not yet fully integrated into students' routines. Tailored training and awareness initiatives could enhance its adoption for personal and academic purposes among university students.